A Survey of interleaving techniques in turbo codes - Devi, M. Rajani; Ramanjaneyulu, K.; Krishna, B. T. (International Journal of Engineering and Technology, 2018)
This paper focuses on the interleaving techniques used in Turbo codes in wireless communications. The performance of turbo codes is measured in terms of Bit Error Rate (BER) versus Signal to Noise Ratio (SNR) and the number of iterations. It tends to increase with better interleaving, better encoding and decoding algorithms. This paper presents the concepts of turbo coding, different interleaving methods and decoding techniques.